Motor imagery in autism: a systematic review - Gowen, Emma; Edmonds, Eve; Poliakoff, Ellen (Frontiers in Integrative Neuroscience, 2024)
Introduction Motor Imagery (MI) is when an individual imagines performing an action without physically executing that action and is thought to involve similar neural processes used for execution of physical movement. As motor coordination difficulties are common in autistic individuals it is possible that these may affect MI ability. The aim of this systematic review was to assess the current knowledge around MI ability in autistic individuals. Methods A systematic search was conducted for articles published before September 2023, following PRISMA guidance. Search engines were PsycINFO, PubMed, Web of Science, Scopus, Wiley Online Library and PsyArXiv. Inclusion criteria included: (a) Original peer-reviewed and pre-print publications; (b) Autistic and a non-autistic group (c) Implicit or explicit imagery tasks (d) Behavioral, neurophysiological or self-rating measures, (e) Written in the English language. Exclusion criteria were (a) Articles only about MI or autism (b) Articles where the autism data is not presented separately (c) Articles on action observation, recognition or imitation only (d) Review articles. A narrative synthesis of the evidence was conducted. Results Sixteen studies across fourteen articles were included. Tasks were divided into implicit (unconscious) or explicit (conscious) MI. The implicit tasks used either hand (6) or body (4) rotation tasks. Explicit tasks consisted of perspective taking tasks (3), a questionnaire (1) and explicit instructions to imagine performing a movement (2). A MI strategy was apparent for the hand rotation task in autistic children, although may have been more challenging. Evidence was mixed and inconclusive for the remaining task types due to the varied range of different tasks and, measures conducted and design limitations. Further limitations included a sex bias toward males and the hand rotation task only being conducted in children. Discussion There is currently an incomplete understanding of MI ability in autistic individuals. The field would benefit from a battery of fully described implicit and explicit MI tasks, conducted across the same groups of autistic children and adults. Improved knowledge around MI in autistic individuals is important for understanding whether MI techniques may benefit motor coordination in some autistic people.